Study of self-drug administration among 3rd professional medical students - Bhushan, Rabi; Chandra, Akash; Verma, Raj Kishore (International Journal Of Community Medicine And Public Health, 2021)
Background: Self-medication is very common in our day-to-day life which is an unhealthy and risky practice. Present study was done to determine the knowledge, attitude and practice among 3rd professional medical students of Shaheed Nirmal Mahto Medical College and Hospital, Dhanbad. Methods: A questionnaire related to self-medication with consent was prepared and distributed among the students of 3rd professional. Data was collected and analysed the results expressed as counts and percentages. Results: Total 50 students participated in the study for taking self-medication and was no need to visit the doctor for minor illness. In maximum students, source of information of the drugs used for self-medication pharmacological based and learning process in the college. The source of drug was medical store. Most of the students took self-medication for loose motion and headache followed by cough, cold and fever. Out of total 50 students, most of the students took paracetamol tablet as self-medication. Conclusions: This study showed that third professional medical students after they studied pharmacological books, they do not use any wrong medicine as self-medication. High level of awareness of 3rd professional students has minimized self-medication.